ENFERMEDADES PROFESIONALES EN EL PERSONAL DE ENFERMERÍA. HOSPITAL GENERAL DOCENTE RIOBAMBA. OCTUBRE 2018-FEBRERO 2019. - Espín Porras, Estefanía Elizabeth (2019)
This research project aimed to describe the occupational risks that trigger professional illnesses in the nursing staff, the Riobamba General Teaching Hospital in the period October 2018-February 2019. Descriptive study, cross-sectional field with a mixed approach. The population consisted of 113 nursing graduates who work in the different services, who participated independently and voluntarily through care, and 15 professionals were excluded who were on vacation and did not want to participate. As a survey and observation has been applied, as an instrument that has been worthwhile by three experts before to the application. Data processing was performed with the Microsoft Excel program of the total population surveyed and observed for the critical services: emergency (22), UCI (8), obstetric center (9), surgical center (9), neonatology (18) and semi-critical: Gynecology- Obstetrics (15), pediatrics (8), outpatient consultation (5), internal medicine (9) and surgery (10). Determining that the predominant gender was the female, most married and the relevant age group composed with ages between 31-40 years, the level of knowledge of occupational health was measured and occupational risks were identified. The relevant results deduced that there is a lack of knowledge of nurses about the criteria that evaluate an occupational disease and do not differentiate the terms of accident and work incident. At the same time it was verified that the risks to which the personnel are most exposed are: biological, ergonomic, psychosocial and environmental.